Language Acquisition among Early Childhood Diaspora: The Role of Indonesian in Malaysia's Kepong Guidance Studio - Putri, Vera; Yeni Rahmawati, Ida; Cahyono, Hadi; Fauzi Nasution, Ikhwan (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
This study investigates the acquisition and development of Indonesian as a second language among early childhood learners within the Indonesian diaspora at the Kepong Guidance Studio in Malaysia. Utilizing a qualitative case study methodology, data were collected through interviews, observations, and documentation involving 21 children aged 4-6 years, their educators, and the principal. Despite the structured Indonesian curriculum, findings revealed that the dominant use of Malay significantly influences language development. Teaching strategies incorporating traditional Indonesian games and songs were found to be effective in enhancing language acquisition. Observational data indicated that 60% of children aged 4-5 years showed significant development in understanding and using Indonesian, while 87.5% of children aged 5-6 years exhibited strong repetition and communication skills in Indonesian. However, challenges included inconsistent language usage and the influence of the children's first language, Malay. The study underscores the necessity of tailored educational strategies that address individual learning needs and emphasize active parental involvement to reinforce language skills acquired in educational settings. Triangulation ensured data reliability and validity, though the small sample size and context-specific nature limit the generalizability of the findings. These results highlight the importance of inclusive and adaptive learning environments that cater to the linguistic and cultural needs of diaspora children. Future research should explore the long-term impacts of these educational strategies on language proficiency and cultural identity, with a broader scope and larger sample sizes to enhance understanding and support effective educational policies and practices for diaspora communities globally.